Evaluation of Joint Regulation of the Minister of Religion and Minister of Home Affairs No. 9 and 8 of 2006: Study on Maintenance of Religious Harmony Policy (Jurnal Bina Praja, 2016)
This study aims to evaluate the implementation of the regulation in the province of East Java. The method used in this study is naturalistic or qualitative with a descriptive explanation. The study result shows that in general, the implementation of the regulation in the province of East Java has not been effective. Factors that affect, among others, are the lack of commitment of in implementing the regulation, weak socialization of the regulation, weak law enforcement,and the lack of multicultural education to the community. The policy that needs to be implemented is mainly of the regulation needs to be improved to become a Law. The approval of the existing Draft Law on the Protection of Religious Community needs to be accelerated.
Keywords: protection; religious harmony; regulation socialization